Leaving education early : putting vocational education and training centre stage - (:unkn) unknown (Publications Office of the European Union, 1970)
"Published in two volumes, the first one is dedicated to understanding better the learning pathways of young students, providing measurements of early leaving in VET, and understanding the role of VET in breaking the vicious cycle of early leaving and unemployment. The second volume reviews VET-related measures to tackle ELET (early leaving from education and training), either by preventing learners dropping out and/or by bringing those who have already left back to education and training." (Editor, BIBB-Doku)
Keywords: I 2.2 Europa; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); G 1.3.2 Bildungsverhalten und -verläufe; Ausbildungsabbruch; Ausbildungsabbrecher; Ausbildungsstellenmarkt; Arbeitsmarkt; Europäische Union; Internationaler Vergleich